Implementasi Pembelajaran Maharoh Istima’ dengan Metode Elektik di Kelas 1 Madrasah Aliyah Pondok Pesantren Islamic Center Bin Baz - Muhammad Syafii Tampubolon; Abdunrorma Sama Alee (At Turots: Jurnal Pendidikan Islam, 2024)
The aim of this research is to determine the implementation of Maharoh Istima' (listening skills) learning using the eclectic method in Class 1 of the Bin Baz Islamic Center Islamic Boarding School. Maharoh Istima' (listening skills) is one of the four language skills (hearing/Istima', speaking/kalam, reading/qira'ah and writing/kitabah) which is taught to students first before being taught the other four language skills. The Maharoh Istima'' subject in Class 1 of Madrasah Aliyah Islamic Center Bin Baz Islamic Boarding School is a subject taught for two semesters over one year. A good Maharoh Istima learning process and appropriate learning methods are needed to obtain maximum results. This research uses a descriptive qualitative approach. The data collection techniques used were interviews, observation and documentation. The research results show that Maharoh Istima' learning at Madrasah Aliyah Islamic Center Bin Baz Islamic Boarding School uses various learning tools including learning objectives, learning materials, learning methods, learning and evaluation media, learning support facilities, as well as various types of evaluation used by teachers in Maharoh learning. Istima'